Emocje w narracjach, czyli o strukturze pojęcia strachu u dzieci w wieku przedszkolnym i wczesnoszkolnym - Jach-Salamon, Natalia (Człowiek i Społeczeństwo, 2023)
The article presents research on the structure and content of the concept of sadness, based on the statements of preschool and early school age children. The research was carried out in a transverse (transversal) system among children selected from six age groups: 4.0−4.11, 5.0−5.11, 6.0−6.11, 7.0−7.11, 8.0−8.11, 9.0−9.11. Data collected from a sample of 240 children were used to analyze the test results. There were 20 girls and 20 boys in each of the six designated age group. In order to describe the content and structure of emotional concepts the experimental technique created by S. Grabias (2012) was used. It allowed to obtain an information on six basic components of a given concept, i.e. definition/definition category, carrier, features, activities, causes, circumstances /effect and in addition his assessment. When describing the emotions of fear, the youngest children mainly used tautological definitions containing synonyms and the oldest ones were dominated by abstract definitions. When talking about the symptoms of emotions, the surveyed children focused primarily on the perceptual indicators of experiencing it. The face and changes in facial expression are particularly significant to them. When describing a person experiencing fear, preschool children mainly referred to typical behaviors related to this emotion, i.e.: afraid, shouting, crying. Analyzes concerning the indications of children for the activities performed by the carrier of the emotion fear show that among the respondents in general, flight from the object of fear was dominant. In the opinion of the surveyed children, the main cause of fear are situations related to the violation of physical body, causing fear and anxiety in humans. Children’s descriptions of reactions to other people’s fear reflect their own tendency to self-regulate, that is, finding ways to deal with experiences. Fear in the perception of the respondents is a negative emotion.